Concept of Studying and Practicing the al-Qur’an - Elsa Nurmalasari; Fatma Husna Haibah Nurulloh; Maya Maridiana; Uus Husni Hoer (Penerbit Hellow Pustaka, 2025)
Expression of the Prophet in the his words خَيْرُكُمْ مَنْ تَعَلَّمَ الْقُرْآنَ وَعَلَّمَهُ need to be examined/investigated its validity in order to generate high motivation for Muslims to practice it. Based on the search results of sanad and Matan of the hadith through many sources and where the focus of the study were Jami at-Tirmidhi, it can be concluded that the quality of hadith was valid. Thus, the Qur'an as a perfect reading for Muslims who has certain rules in reading, from the mention of the letters, the short or the length, the thickness and the provisions of makharijul of letters need to be learned and taught diligently and earnestly. Learning alQur'an includes efforts to learn how to read them, to translate and to understand the laws, the lessons, the instructions contained therein. Likewise, teaching alQur'an includes efforts to lead and guide people to read, to translate and to understand the content of the verses of al-Qur'an. People who do it sincerely and earnestly will get the primacy of the al-Qur'an in the form of tranquility, peace of heart and mind as well as the intercession in the Hereafter.